Chester Raccoon and the almost perfect sleepover - Penn, Audrey, 1947- (Penn, Audrey, 1947- Kissing hand., 2017)
"Chester Raccoon goes to his first sleepover and enjoys a day of fun and games with his friends. But when it is time to go to sleep, Chester feels his mother's love through his Kissing Hand, but still misses his home. Chester goes home and Mrs. Raccoon assures him he came home at just the right time"--